IMPLEMENTASI PEMBELAJARAN INKUIRI PADA BIDANG STUDI AQIDAH AKHLAK - Sariah Sariah (POTENSIA: Jurnal Kependidikan Islam, 2017)
This research raises the problem of the implementation of inquiry learning in the aqidah akhlak subject in Madrasah Aliyah Muhammadiyah Pekanbaru, by raising the research question: how to implement inquiry learning in the aqidah akhlak subject in Madrasah Aliyah Muhammadiyah Pekanbaru. The purpose of this study is to get an overview of the implementation of inquiry learning in the aqidah akhlak subject in Madrasah Aliyah Muhammadiyah Pekanbaru. This research uses qualitative approach with descriptive method. Intruments of data collection include observation, interviews and documentation. The subject of this research is teacher of the aqidah akhlak subject and the object is the implementation of inquiry learning in the aqidah akhlak subject. The technique of data analysis by following steps of data reduction, data display, conclusion, and verification. The results revealed that in the implementation of inquiry learning in the aqidah akhlak subject in Madrasah Aliyah Muhammadiyah Pekanbaru required good innovation of planning, strategy, selection of methods that vary with the right material in accordance with the needs of students and adapted to existing facilities and infrastructure. The findings of this study resulted in recommendations: (1) to teachers in the aqidah akhlak subject may improve the quality of learning, among others, with the ability to use various methods, strategies, and careful planning; (2) to the school would be able to give motivation to students for discipline, serious in learning and have not enough textbooks with LKS alone, because without participatory student implementation of inquiry learning can not optimal.